Adults Users Concerns about their Data Privacy in Social Networking Platforms: A Study of Facebook, Twitter, Instagram and Snapchat. - Alshammari, Abdulelah (2018)
The platforms for social network can be described as online websites or applications whose focuses are directed towards the development of online communities of people with an identical interest or other inclinations, as well as interest with regards to communication and interest exploration and activities of others. The characterisation of these social networking platforms comes in the form of communicating in real-time throughout the entire virtual communities by way of information and picture sharing, together with sharing other information of interest. There is so much richness in the personal data of these online platforms, in a way that has not been seen, so much that any individual with just a click of the button would have the ability of gaining access to a trove of data that comes in the form of digital pictures and videos, and the rest. As a result of these data's fluidity, a possible danger lurks considering the fact that an individual could possibly lose control over such data once they become stored in these servers or networks platforms The aim of this dissertation is centred into the degree of concern that adult's users have regarding their information on four primary social networking platforms of Facebook and Twitter, together with Instagram and Snapchat, and with functionality of these platforms being different. The dissertation will also conduct a secondary data method that investigation adults concerns in these social networking platforms. As a result, this dissertation finds that it is agreed in the research question that the extent of concern over privacy among social network adults' users is growing wider as negative reports and criminal and unauthorized use of personal information rises. Thus, it is strongly recommended that social network platforms to consider these user concerns and do not abuse users' data, in order to have harmonious interactions.